Memoirs of the Dukes of Urbino, Volume 2 (of 3) : Illustrating the Arms, Arts, and Literature of Italy, from 1440 To 1630. - Dennistoun, James, 1803-1855; Hutton, Edward, 1875-1969 (Salt Lake City, UT : Project Gutenberg, 2013)
"Memoirs of the Dukes of Urbino, Volume 2" by James Dennistoun is a historical account written in the mid-19th century. The book provides an in-depth exploration of the lives, politics, and cultural contexts surrounding the Dukes of Urbino from the 15th to the early 17th century, focusing particularly on figures like Guidobaldo di Montefeltro and Cesare Borgia. It highlights the influence of these leaders on the evolution of Italian arts and literature during the Renaissance period. At the start of the memoir, the narrative delves into the dark days surrounding the infamous massacre of Sinigaglia, which reflects both the treachery and brutal political maneuverings of the time. The text portrays the ambitious Borgia family, particularly Cesare Borgia, who orchestrated the downfall of his rivals, showcasing the ruthlessness that characterized their ascent to power. The initial chapters outline the profound implications of this power struggle for the region's citizens and the overall political landscape of Italy, setting the stage for the examination of the renaissance of arts and letters that followed under Duke Guidobaldo's rule. (This is an automatically generated summary.)
Release date is 2013-11-21
E-text prepared by Suzanne Lybarger, Linda Cantoni, and the Online Distributed Proofreading Team (http://www.pgdp.net) from page images generously made available by Internet Archive/Canadian Libraries (https://archive.org/details/toronto)
Keywords: Renaissance -- Italy; Urbino, Dukes of; Nobility -- Italy -- History; Urbino (Italy)